2014
DOI: 10.1021/np500537x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mechanisms of Acacetin against d-Galactosamine and Lipopolysaccharide-Induced Fulminant Hepatic Failure in Mice

Abstract: This study examined the hepatoprotective effects of acacetin (1), a flavonoid isolated from Agastache rugosa, against d-galactosamine (GalN) and lipopolysaccharide (LPS)-induced fulminant hepatic failure. Mice were given an intraperitoneal injection of 1 (25, 50, and 100 mg/kg), or the vehicle alone (5% dimethyl sulfoxide-saline), 1 h before GalN (800 mg/kg)/LPS (40 μg/kg) treatment and sacrificed at 6 h after GalN/LPS injection. GalN/LPS markedly increased mortality and serum aminotransferase activity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…The techniques for isolation and separation of both compounds are simple and easy to operate. The acute toxicity experiment of acacetin showed that it was a safe clinical medication (LD 50 = 933 mg/kg) [ 26 ]. The acute toxicity test of tilianin had not been done yet and there was no report about its toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques for isolation and separation of both compounds are simple and easy to operate. The acute toxicity experiment of acacetin showed that it was a safe clinical medication (LD 50 = 933 mg/kg) [ 26 ]. The acute toxicity test of tilianin had not been done yet and there was no report about its toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…(mustard sponge), 6-undecylsalicyclic acid ( 3 ) and 6-tridecylsalicylic acid ( 4 ) from Caulocystis cephalornithos (marine brown alga), 6-hydroxy-2,5-dimethoxy-9-phenylphenalen-1-one ( 5 ) from Haemodorum spicatum (bloodroot), fuliginosin A ( 6 ) and anigopreissin A ( 7 ) from Macropidia fuliginosa (black kangaroo paw), and acacetin ( 8 ) from Agastache rugosa (Korean mint). These compounds have been shown to possess anti-inflammatory, anti-cancer and/or antimicrobial properties [ 29 , 33 , 34 , 35 , 36 , 37 ]; the latter properties suggest that some of these compounds might also have activities against pathogens such as parasites. In the present study, we explored the activity of select secondary metabolites against H. contortus using established in vitro methods, with the aim of identifying candidate compounds to optimise and develop as anthelmintic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…LPS/GalN-induced mice liver injury model has been widely used to evaluate the biological activities of hepatoprotective agents [ 21 ]. In this study, we evaluated the protective effects of shikonin on liver injury using this model.…”
Section: Discussionmentioning
confidence: 99%